Pengaruh der dan mtbv serta ukuran perusahaan terhadap penggunaan instrumen derivatif sebagai pengambilan keputusan hedging - Yusvika Rachmawati; Djoko Setyadi; Rizky Yudaruddin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to predict the probability of the effect of variable debt to equity ratio, market to book value, and firm size to the use of derivative instrument as hedging decision making in companies listed on the Indonesia Stock Exchange in 2009-2014.The study population of 142 companies listed in the Indonesia Stock Exchange. The sampling method used is purposive sampling method, in order to obtain 17 companies sampled for 6 years of observation (2009-2014) with 102 observation. Data were obtained from financial statements that have been published and downloaded from the website of the Stock Exchange that www.idx.co.id. Data analysis technique used is descriptive statistical analysis and logistic regression analysis. The process of data analysis done first is descriptive analysis and hypothesis testing.The results of analysis concluded that the debt to equity ratio and firm size predicted not significant influence on decision making hedging. Market to book value is predicted to have a positive influence on the decision making and hedging. Keyword: hedging, derivatives, debt  to equity ratio, market  to book  value,and firm size.